Radiation use efficiency, biomass production and grain yield of heat tolerant summer maize (Zea mays L.) hybrids in subtropical environment - Subrahmanyam, K; Umesh, MR; Ananda, N; Kuchanur, Prakash H; Ajayakumar, MY; Chittapur, BM (Bangladesh Journal of Botany, 2021)
Radiation use efficiency (RUE), heat use efficiency (HUE), biomass production and grain yield of contrasting heat tolerant summer maize hybrids and irrigation regimes during hot summer in subtropics of India were assessed. Experiment was conducted with RCRMH-1, RCRMH-2 and Arjun hybrids under well-watered based on 1.0 IW/CPE (I1), mild stress at 0.75 IW/CPE (I2) and severe stress at 0.5 IW/CPE (I3). Results indicated that RCRMH-2 outyielded 13.3 and 26.4% over RCRMH1 and Arjun, respectively. In well-watered (I1) plots all the hybrids performed better than other irrigation regimes I2 and I3. Among hybrids RCRMH-2 showed lower grain yield reduction under water stress condition. While RUE of RCRMH-2 under I1, I2 and I3 were 1.93, 1.72 and 1.53 g/MJ, respectively. It also showed higher biomass production, LAI and HUE over rest of the hybrids. Radiation, water and heat use efficiencies, yield attributes and yield were higher in January sown plants.